Surface Quality Investigation of Al 6061-T6511 Using TiAlN Coated Milling Tool - Sivarao, Subramonian; Fairuz, Dimin; T., Joseph Sahaya Anand; Jamil, Ridzuan; Ahmad , Kamely (IJENS, 2010)
The study of machining conditions in the machining of alloys is important in quantifying its effects on the overall surface roughness produced by the pre-determined parameters. Material removal processes such as CNC end milling requires an understanding in the machining conditions and setup to achieve a certain targeted finish of the work surface. Machining conditions such as depth of cut, feed rate, cutting speed, cutting tool geometry, material and tool properties play a decisive role in the outcome of the surface roughness. Augmentations to the above mentioned conditions might enhance or have a detrimental effect on the surface finish quality. This work investigates the effects of varying depth of cut which could have significant effect on the surface roughness of Al 6061-T6511 work material by implementing the use of TiALN coated carbide tool using HAAS CNC milling. The outcome clearly witnesses that depth of cut has got significant effect on the surface quality of end product within the range of experimental values.